Composation of Polyaluminum Chloride with Hydroxyapatite and Its Application for Separation of Hexavalent Chromium Ions - Basril Simbarta Tarigan; Rukiah Rukiah; Atiek Rostika Noviyanti (Balai Besar Keramik, 2021)
Chromium is the dominant heavy metal in liquid waste from the leather tanning industry, wood preservation and textile processing. Generally chromium waste is found as trivalent and hexavalent chromium ions. Hexavalent chromium ion is dangerous for humans because of its carcinogenic nature, which can lead to skin irritation, lung cancer, kidney and stomach disorders. Coagulation-flocculation (CF) is a method used to reduce hexavalent chromium ion levels. Polialuminum chloride (PAC) has been widely used in water treatm ent using the CF method. Unfortunately, however, the PAC stability is poor, the coagulation efficiency is low, and the floc formation time is slow. In addition, PAC can produce Al3+ which is toxic in processed water. But its toxicity can be overcome by adding donor ligands that contain oxygen such as hydroxides, carboxylic acids and phosphates, such as hydroxyapatite (HA). In addition, the addition of HA with the optimum composition and pH at PAC can increase the performance of PAC. This study aims to optimize the PAC/HA combination at various pH so as to reduce the concentration of hexavalent chromium ion, controlled by UV-VIS spectroscopy. The highest reduction in Cr (VI) ion content was obtained by PAC, but the highest stability was obtained by the composition of PAC/HA 4: 6.